A Cephalometric Study of the Sella Turcica in a 7–13‐Year‐Old Group: A Proposal for Age Estimation in Badly Preserved Sub‐Adult Skeletal Remains. (11th December 2015) - Gibelli, D. M.; Cerutti, E.; Spagnoli, L.; De Angelis, D.; Mattia, M.; Zago, M.; Cattaneo, C.; Sforza, C.
Abstract : Age estimation is a relevant field of application in archaeology, which is often limited by the fragmentation of recovered skeletal remains. There is therefore an urgent need for the development of novel methods. A potentially useful bone district is the sella turcica. The aim of this study was to evaluate the metrical standards of three different measurements of the sella turcica (length, depth and diameter) in 177 lateral cephalometric radiograms belonging to male and female individuals aged between 7 and 13 years, in order to find standards useful for age estimation. The results were evaluated by two‐way ANOVA. There was no significant interaction between sex and age in any variable. The linear regression model fitted to the age and diameter measurements yielded the following equation: age (years) = 4.14*diameter (cm) + 5.76. Slope and intercept 95% CIs were, respectively, 4.64–7.61 years per centimetre and 2.34–5.28 years. The relevant coefficient of determination was R 2 = 0.15, while the root mean square error was 1.74 years. The present results provide a novel method that is useful for the age estimation of skeletal remains recovered in archaeological contexts: further studies are needed in order to improve the method on a larger sample.